Illocutionary Acts Forces of Tsunami's Victims in Central Celebes 2018 - Irwan Rohardiyanto (Metaphor, 2019)
This study elaborates the utterances spoken by Tsunami's Victim in Central Celebes. It focuses on the exclamatory speech acts. There are kinds of utterances cried by victim especially video or audio taker when the tsunami occurred in the end of September 2018. The disaster destroys the city of Palu, Donggala regency, Parigi Moutong Regency, and Mamuju Utara Regency of Central Celebes. This study is expected to get the kind of Illocutionary Speech Acts especially illocutionary acts forces and the function of those. The kinds of illocutionary acts frequently appeared are expressive and declarative. The function of the illocutionary acts in a panic circumstance are informing, commanding, asking, requesting, shouting, wishing, expecting, complimenting as well as blaming.